Serum salusin levels in diarrhea- and constipation-predominant irritable bowel syndrome - Elif Tugba Tuncel; Seda Sabah Ozcan; Mehmet Korkmaz; Elif Börekci (PeerJ)
Objective Inflammation and immunity play major roles in the etiopathogenesis of functional intestinal disorders. The salusins that were identified in this study are important because of their ease of collection, sensitivity and reliability. For that reason, the aim of this study was to analyze the importance of the levels of salusin in the blood, an inflammation-related parameter, in the diagnosis and prediction of irritable bowel disease. Methodology The study participants included 28 diagnosed with constipation-predominant IBS, 29 (34.1%) diagnosed with diarrhea-predominant IBS (D-IBS), and 28 (32.9%) controls. Enzyme-linked immune-sorbent assay (ELISA) method has been used for the measurement of salusin levels. Results Participants were 50 (58.8%) female and 35 (41.2%) male. The serum levels of salusin-α were substantially reduced in the diarrhea-predominant IBS group vs controls. There was also no major difference in the levels of salusin between the constipation-predominant-IBS and the diarrhea-predominant IBS group. Conclusion A major prognostic relationship was found between the level of salusins and the subgroup of D-IBS. It is well known that salusins have been related to inflammatory processes and oxidative injury in previous studies. The relationship between salusin and gastrointestinal diseases should be further investigated. Low-grade submucosal intestinal inflammation is also associated with irritable bowel syndrome. It is our belief that salusins may be useful in diagnosing, predicting or treating IBS.